Are you a doctor? … Are you a doctor? I'm not a doctor! A reappraisal of mitigated echolalia in aphasia with evaluation of neural correlates and treatment approaches. Issue 7 (3rd July 2018) - Berthier, Marcelo L.; Torres-Prioris, María José; López-Barroso, Diana; Thurnhofer-Hemsi, Karl; Paredes-Pacheco, José; Roé-Vellvé, Núria; Alfaro, Francisco; Pertierra, Lucía; Dávila, Guadalupe
ABSTRACT: Background : Mitigated echolalia (ME) is a symptom of aphasia which refers to a seemingly deliberate repetition of just-heard words and phrase fragments. ME has historically been viewed as a compensatory strategy aimed to strengthen auditory comprehension. Nevertheless, this hypothesis and other possible functional deficits underlying ME have not been evaluated so far. Aims : This study aimed to (a) reappraise ME in the frame of modern neuroscience; (b) report the effects of Constraint-Induced Aphasia Therapy (CIAT) and a cognition-enhancing drug (memantine) on detrimental ME in a patient (CCR) with fluent aphasia; and (c) analyse the functional and structural brain correlates of ME in CCR with multimodal neuroimaging. Methods & Procedure : Tasks tapping verbal expression and auditory comprehension were administered to CCR to evaluate ME. After baseline testing, evaluations were performed under placebo alone (weeks 0–16), combined placebo with CIAT (weeks 16–18), placebo treatment alone (weeks 18–20), washout (weeks 20–24) and memantine (weeks 24–48). Instructions to reduce ME during CIAT were provided to CCR. Language evaluation and multimodal neuroimaging were also performed 10 years after ending treatment. Outcomes & Results : At baseline, ME occurred in spontaneous speech and in difficult-to-understand single words, indicating impaired meaning access. However, more instances of ME were heard in sentence comprehension, reflecting additional impairment in short-term memory. ME also occurred in words that were correctly defined and understood to the extent that even after accessing word meaning successfully, CCR repeated the same word several times, suggesting impaired inhibitory response control. In comparison with baseline, analysis of auditory sentence comprehension under treatment revealed significant decrements of ME just after ending CIAT and 2 weeks later. These gains were maintained under memantine 6 months later. No changes in ME were found during both placebo and washout phases. Instructions to constrain ME reduced the time to complete a sentence comprehension task 2 weeks after CIAT. ME returned to baseline levels 10 years later. Multimodal imaging suggested that ME in CCR resulted from residual activity of remnants of the left dorsal stream and the intact right white matter tracts after extensive damage to the left ventral stream. Conclusions : ME in CCR interfered with functional communication, and it may be attributed to deficits in sound-meaning mapping, auditory short-term memory, attentional control, and inhibition of repetition mechanisms. Our preliminary evidence suggests that ME, in patients like CCR, may be modulated with specific instructions during aphasia therapy and drugs.